Relationship between Atherogenic Index of Plasma (AIP) and Mayor Cardiovascular Event (MACE) in Patients with Acute Myocardial Infarction (IMA) with Percutaneous Coronary Intervention (PCI) in Haji Adam Malik Hospital - Ramzi, Defriyan; Hasan, Refli; Safri, Zainal (Journal of Society Medicine, 2024)
Introduction: Atherogenic index of plasma (AIP) is a new biochemical parameter closely related to lipid metabolism in the body as a risk factor in atherosclerosis and coronary heart disease. This study aimed to determine whether AIP values could be used to predict major cardiovascular events (MACE) in the treatment period of ACS patients undergoing primary percutaneous coronary intervention processes. Methods: This study was an observational analytical study with retrospective data collection method. Patients who experienced ACS  at RSUP Haji Adam Malik Medan and undergo IKP starting from April 2023 will be collected. Basic characteristic data including laboratory parameters and AIP values as well as MACE events were be collected. Data analysis were carried out whether there are differences in AIP values in MACE and Non-MACE patients, and predictive ability will be assessed through ROC/AUC curve analysis, and sensitivity and specificity values will also be obtained. Results: A total of 69 samples were obtained. A total of 25 patients (36.2%) experienced MACE. The most prevalent MACE in this study was death from all causes as many as 17 patients (24.6%). AIP value can be used as a predictor of MACE events:  Death of All Causes (Cut Off value: 0.505; AUC: 0.673; P = 0.033; 95% CI 0.537 – 0.809; Sensitivity 64.7%; Specificity 59.6%), Acute Heart Failure (Cut Off value: 0.502; AUC: 0.695; P = 0.029; 95% CI 0.551 – 0.839; Sensitivity 69.2%; Specificity 60.7%), and Malignant Arrhythmia (Cut Off value: 0.582; AUC: 0.758; P = 0.026; 95% CI 0.578 – 0.938; Sensitivity 71.4%; Specificity 75.8%). Conclusion: The AIP index can be a good predictor of the incidence of MACE in ACS patients undergoing primary percutaneous coronary intervention.